Psychology for teaching - Lefranc'ois, Guy R. (Wadsworth Pub. Co., 1997)
Psychology for teaching, An overview of development, Cognitive and personality development, Behaviorism and social cognitive theory, Thinking and remembering, Cognitive instructional models...